Quantitive assessment soil erosion by USLE and GIS in mountains and hills, Thanh - Nghe - Tinh region - Dung, Nguyen Van; Ky, Nguyen Dinh (Vietnam Journal of Earth Sciences, 2012)
In the hills and mountains of Thanh - Nghe - Tinh region, rapid population growth, social - economic pressure and reasonable land use are main impact on soil erosion increasing both scale and intensity. It makes land degradation and affect agricultural production seriously. The present research integrated Universal Soil Loss Equation (USLE) and Geography information system (GIS) to measures soil erosion. Each of factors in the USLE was estimated and built in a GIS database to create the erosion factor layers. Soil erosion layer was built from overlay operation with the USLE model and grouped into 5 classes of soil loss, from weak level to catastrophic level. The result shows that modest soil erosion, from 2 to 5 t/ha/yr, is 11,04 % of nature area of Thanh - Nghe - Tinh region; strong - modest soil erosion, from 5 to 10 t/ha/yr, is 8,75 % nature area; strong soil erosion, from 10 to 20 t/ha/yr, is 8,46% nature area; catastrophic and extremely strong soil erosion, greater than 20 t/ha/yr, is 16,05% nature area. These areas should be priorities for policy and appropriate land use planning to control soil erosion in soil loss tolerance.